Fruit and seed ontogeny and its taxonomic relevance for Vernonieae (Asteraceae) - Voltolini, Caroline Heinig; Oliveira, Fernanda Maria Cordeiro; Souza, Luiz Antonio de (Acta Scientiarum. Biological Sciences, 2024)
In the Asteraceae the pappus and cypsela provide many important structural features that are of potential taxonomic significance. Vernonia is a revised genus that has recently undergone a rearrangement consisting of the genera Vernonia s.s., Chrysolaena, Lepidaploa, Lessingianthus and Vernonanthura. In the present investigation, the cypsela ontogeny of species of these genera and of the monospecific Orthopappus was analyzed. Our study is an attempt to show that the anatomical features of the fruit (pericarp and seed) have taxonomic value within the tribe. Flowers and fruits in development were analyzed using a light microscope and scanning electron microscope. The persistent fruit pappus is bristly and biseriate. The mature pericarp is usually composed of more or less collapsed exocarp and sclerenchymatous mesocarp. At this stage, the mature seed coat is unspecialized; the unlayered endosperm and collapsed endothelium persist. Some features regarding the pappus, cypselae, and seeds have provided support to separate the segregated species of Vernonieae, especially when they are compared to the Orthopappus angustifolius.